2015
DOI: 10.1007/s40617-015-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Another Perspective on Research as a Measure of High-Quality Practitioner Training: a Response to Dixon, Reed, Smith, Belisle, and Jackson

Abstract: Dixon et al. ( 8:7-15, 2015) argued that the research productivity of behavior analytic graduate programs may be a reasonable criterion to evaluate training program quality. They reviewed the cumulative publications of graduate programs. From this analysis, they generated a top ten list of graduate programs with the greatest number of faculty publications and, because of the number of these publications, inferred that they may be better training programs than those not on the list. We countered that the qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…During our own data collection, we observed that the article count generated by a specific search could vary somewhat from day to day. 1 Consequently, we are not surprised that several commentators proposed alternative metrics for evaluating scholarly productivity (e.g., Maguire and Allen 2015;Wilder et al 2015), and we concur with them that details of faculty productivity rankings will vary as a function of the specific metrics employed. 2 We are nearly as certain, however, that any credible metric will lead to replication of our main findings, that most ABA faculty do not publish much.…”
Section: Mission Accomplishedmentioning
confidence: 53%
See 1 more Smart Citation
“…During our own data collection, we observed that the article count generated by a specific search could vary somewhat from day to day. 1 Consequently, we are not surprised that several commentators proposed alternative metrics for evaluating scholarly productivity (e.g., Maguire and Allen 2015;Wilder et al 2015), and we concur with them that details of faculty productivity rankings will vary as a function of the specific metrics employed. 2 We are nearly as certain, however, that any credible metric will lead to replication of our main findings, that most ABA faculty do not publish much.…”
Section: Mission Accomplishedmentioning
confidence: 53%
“…Only upon accepting this discouraging (to us, at least) truth about the research productivity of those most responsible for disseminating our field's knowledge to its next generation, we can move on to the corollary issuedoes the research productivity of ABA faculty really matter in practitioner training. Several commentators (e.g., Detrich 2015;Maguire and Allen 2015) suggested that low faculty research productivity does not necessarily signal that a training program is inferior. This is a point worthy of debate, and it can only be good for our field to evaluate how specific training experiences impact professional competency.…”
Section: Mission Accomplishedmentioning
confidence: 99%
“…The intention was for these experiences to serve as touchstones for students which allowed them to connect data points on a graph to lived experience, ideally making them more discerning and critical consumers of research and capacitating them to conduct unique research to resolve problems in their own practice (cf. Critchfield, 2015; Dorsey & Harper, 2018; Maguire & Allen, 2015).…”
Section: Supervised Field Experiences At Vanderbilt Universitymentioning
confidence: 99%
“…Ideally, these efforts are accompanied by valid measurement systems capable of facilitating data‐informed programmatic evolutions. However, specific methods of evaluation have yet to be agreed upon (e.g., Ahearn et al, 2015; Carr & Nosik, 2015; Detrich, 2015; Dixon et al, 2015a, b; Hayes, 2015; Hineline, 2015; Iwata, 2015; Maguire & Allen, 2015; Pritchard & Wine, 2015; Reeve, 2015; Wilczynski, 2015; Wilder et al, 2015).…”
mentioning
confidence: 99%